Systems Convening in Landscapes of Interprofessional Education Practice (Journal on Excellence in College Teaching, 2024)
This case study explores leadership emergence within a faculty-based community of practice engaged in a scholarly interprofessional education initiative between nursing, medical, and clinical simulation educators within a transnational higher education context in the Middle East. Findings in this qualitative study revealed rich insights into the inner mindset of an interprofessional education systems convener as applied to the four dimensions of Wenger-Trayner and Wenger Trayner’s (2021) theoretical model. The study identifies and presents the role and salient capacities of a systems convener in attempting to reconfigure professional identities within a unique interprofessional education landscape of practice.